Algorithmic Governance: Unveiling the Nexus between Artificial Intelligence and Policy Dynamics - Ijaz, Muhammad (Annals of Human and Social Sciences, 2024)
It's commonplace for artificial intelligence (AI) to be incorporated into government worldwide these days. The objective of this research is to understand and scrutinize the relationship between policymaking and postmodern conceptions and inventions of AI and Algorithmic Governance. In the modern world, incorporation of the AI and technology into the processes of policymaking and governance is indispensable. Therefore, research needs to be conducted on this scenario as to analyze the relationship between policy dynamics and incorporation of AI into it. This research employs a qualitative approach, entailing case studies and consequent analyzation to demonstrate the connection of AI and governance. The research finds that the nexus between AI and policy dynamics in light of the algorithmic governance encompasses a wide variety of aspects, including fostering community participation, increasing policy effectiveness as well as considering the ethical boundaries. In the end, this work advances our understanding of the complex relationships between AI technology and policy dynamics, which may be helpful to researchers, policymakers, or other organizations traversing algorithmic management environments.